Endogenous Growth and Cross-Country Income Differences - Howitt, Peter (American Economic Review, 2000)
A multicountry Schumpeterian growth model is constructed. Because of technology transfer, R&D-performing countries converge to parallel growth paths; other countries stagnate. A parameter change that would have raised a country's growth rate in standard Schumpeterian theory will permanently raise its productivity and per capita income relative to other countries and raise the world growth rate. Transitional dynamics are analyzed for each country and for the world economy. Steady-state income differences obey the same equation as in neoclassical theory, but since R&D is positively correlated with investment rates, capital accumulation accounts for less than estimated by neoclassical theory. (JEL E10, O40)